2014
DOI: 10.1002/adma.201401389
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport in Polycrystalline Graphene: Challenges and Opportunities

Abstract: Graphene has attracted significant interest both for exploring fundamental science and for a wide range of technological applications. Chemical vapor deposition (CVD) is currently the only working approach to grow graphene at wafer scale, which is required for industrial applications. Unfortunately, CVD graphene is intrinsically polycrystalline, with pristine graphene grains stitched together by disordered grain boundaries, which can be either a blessing or a curse. On the one hand, grain boundaries are expect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
186
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(190 citation statements)
references
References 100 publications
(294 reference statements)
4
186
0
Order By: Relevance
“…GB G , where R S is the sheet resistance of the polycrystalline sample, R S 0 is the sheet resistance within the grains, and l G is the average grain size [26].…”
Section: Electrical Resistivity Of Individual Gbsmentioning
confidence: 99%
“…GB G , where R S is the sheet resistance of the polycrystalline sample, R S 0 is the sheet resistance within the grains, and l G is the average grain size [26].…”
Section: Electrical Resistivity Of Individual Gbsmentioning
confidence: 99%
“…Note that CVD-grown graphene is intrinsically polycrystalline, with graphene grains stitched together by grain boundaries that act as a source of intrinsic carrier scattering and degrade the electrical properties. [106] Thus, one promising approach is to reduce the number of grain boundaries by growing large-size grains or even a single crystal film to improve the optoelectrical performance of graphene TCFs, but this remains a great challenge. [103,107] The transfer process of etching away the copper not only leads to inevitable damage to the graphene, the production of metal residues and serious environmental pollution, it also increases production cost.…”
Section: Graphene Transparent Conductive Filmsmentioning
confidence: 99%
“…9. It follows that the expected effective sheet conductance normalized to the intra grain sheet conductance becomes…”
Section: A Effective Sheet Conductancementioning
confidence: 98%
“…GBs are presently ubiquitous in CVD processed material since the technique relies on stitching together-initially separate-grains in order to achieve larger coherent sheets. 5 Both theoretical 6,7 and experimental studies 8,9 on transport through graphene GBs found that GBs cause potential barriers for the carrier transport and result in an increase in resistance, which sometimes is 30 times larger than the bulk graphene resistance at the center of the grain. [10][11][12] Thus, the GBs are significantly deteriorating the electrical properties of the films, which in turn affect the performance of graphene based devices, e.g., field-effect transistors.…”
mentioning
confidence: 99%